Sensitivity comparison of nested RT-PCR and TaqMan real time PCR for intravitam diagnosis of rabies in animals from urine samples - N. K. Sood; D. Deka; K. Bansal; C. K. Singh; V. Ramneek; M. Dandale (Veterinary World, 2013)
Aim: Early diagnosis of dreadful rabies is of utmost importance to restrict number of contacts and timely administration of post exposure prophylaxis. The present study was conducted to evaluate the sensitivity comparison of Nested RT-PCR with TaqMan real time PCR technique for intravitam diagnosis of rabies in animals from urine samples. Materials and Methods: Advance molecular approaches Nested RT-PCR and TaqMan real time PCR was employed on 21 urine samples for intravitam diagnosis of rabies. Comparison of both the techniques was done with standard immunofluorescence test (FAT) applied on brain for postmortem confirmation of rabies. Result: Rabies viral RNA was detected in 6/21 (28.57%) and 11/21 (52.38%) urine samples by application of Nested RT-PCR and TaqMan real time PCR respectively. Sensitivity obtained from both the techniques was 62.50% and 78.94% respectively when compared with gold standard immunofluorescence test (FAT). Conclusion: TaqMan real time PCR can serve as more sensitive and viable approach for the intravitam diagnosis of rabies as compared to Nested RT-PCR for detection of rabies from urine of suspected animals. Clinical importance: This study may serve as background for future intravitam rabies diagnostics. [Vet World 2013; 6(4.000): 189-192]